Theory of Mössbauer effect in intermediate-valence compounds. - Balseiro, Carlos Antonio; Alascio, Blas Rafael; Lopez, A. (American Chemical Society, 1979)
Fil: Balseiro, C. Comisión Nacional de Energía Atómica; Argentina